THE IMPORTANCE OF ASSESSMENT IN THE ESP CLASSES (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article considers information about the importance of assessment in ESP classes, the role of English language in today’s world of education and the significance of the creative approach of the teacher during the lesson in order to mark students’ participation. Creativeness of the teacher for assessment is one of the important teacher’s professional characteristics. This is because, an appropriate rating system may inspire the students to be interested in subject. The better teacher use skilfully different techniques of marking like methods, the easier it may be for them to make more active the learners at teaching process. Namely, this can be a motivation for the ESP students who have not desire to acquire English perfectly as their main subject.